PS16 Which is more Effective, A Universal or Targeted Approach, to Implementing the National Healthy Start Programme? A Mixed Methods Study. (17th September 2012) - Moonan, M; Hanratty, B; Whitehead, M
Abstract : Background: Healthy Start is a statutory scheme in the UK, aiming to improve the health of children and pregnant or lactating women by providing food vouchers and vitamins. The Department of Health intended the intervention to be targeted to low incomes families (a targeted approach), but in some areas Healthy Start vitamins are available to eligible mothers and children independent of income (a universal approach). The aim of this study is to investigate which approach is more effective and to identify barriers to implementation. Methods: 1) Systematic review of the literature to identify which approach, universal vs. targeted, achieves the highest coverage of vitamin use in pre-school children and pregnant women.; 2) Using national data, a comparison of vitamin uptake rates in targeted and universal areas.; 3) In depth qualitative interviews with 30 commissioners, providers and service users from a targeted and universal area. Data were thematically analysed. Results: 1) Initial findings from the systematic literature review reveals that universal supplementation of vitamins such as folic acid significantly reduces the incidence of preventable ill health due to vitamin deficiencies such as neural tube defects compared to a targeted approach.; 2) In areas using the targeted approach, the uptake of children's drops and women's tablets was 1.46% and 2.56% respectively. In the area that adopted a universal approach, the uptake of children's drops and women's tablets was 3.97% and 7.72% respectively. ; 3) Barriers shared by both approaches include a lack of awareness of the scheme amongst health professionals, onerous administrative processes and the availability of vitamins. The universal approach is supported by health professionals because it does not stigmatise recipients. Conclusion: 1) From the systematic review, mandatory universal fortification of foods, e.g. flour is a major public health opportunity for the UK.; 2) Uptake of Healthy Start food vouchers and vitamins is low whatever the implementation strategy. However, uptake of Healthy Start vitamins is significantly higher in areas adopting a universal approach to implementation. A universal approach to implementation is supported by the literature and this study suggests that it may overcome some barriers to the implementation of the Healthy Start scheme nationally.; 3) In particular, a universal approach may reduce some of the administrative hurdles confronted by a targeted approach and will also address the stigma associated with the use of Healthy Start vitamins. Producing evidence for the cost effectiveness of the scheme will be critical for its continued support.